Eosinophilic mastitis: a rare benign inflammatory condition and review of the literature. Issue 10 (12th October 2022) - Arnott, William; Leong, Gregory; Davis, Arie; Diab, Jason; Clement, Zackariah
Abstract: We report the case of a 53-year-old nulliparous female presenting with a 9-month history of recurrent mastitis and a retro-areolar lesion. Histological assessment showed an inflammatory infiltrate predominantly composed of eosinophils without evidence of malignant changes. The patient was diagnosed with eosinophilic mastitis and commenced on a course of oral steroids with good effect. This case will outline the pathology, clinical manifestations and diagnosis of eosinophilic mastitis alongside a review of the literature.